(untitled) (Open Academia: Journal of Scholarly Research, 2023)
In this article, the effect of teacher training on the learning of elementary school students to increase the level of English language proficiency . Information is given that foreign languages are an important component of professional education in a religious society, and the teacher creates that environment depending on the topic .